(untitled) (Orinoquia, 2016)
A 1-year-old male Cocker Spaniel, weighing 10.5 kg, was referred for elective orchiectomy. An intratesticular injection of lidocaine was performed as a part of multimodal anesthetic protocol that also included: acepromazine, meloxicam, tramadol and ketamine. During the intraoperative period the cardiorespiratory parameters (heart rate, respiratory rate, and mean arterial blood pressure), the intraoperative anesthetic (ketamine) and analgesic (fentanyl) consumption, and the presence of autonomous nociceptive responses were evaluated. Increases of baseline cardiorespiratory parameters above 10% or the presence of autonomous nociceptive responses would be considered as indicative of insufficient analgesic coverage, for which 1 μg/kg IV of fentanyl would be employed. The evaluated cardiorespiratory variables were stable, and no autonomous nociceptive responses were observed. For this reason no additional ketamine boluses nor rescue analgesics were administered. It is suggested that intratesticular lidocaine, as a part of the multimodal analgesic protocol employed, contributed to improve the analgesic coverage during orchiectomy in this dog.